A fuzzy goal programming approach with priority for channel allocation problem in steel industry - Tsai, Kune-Muh; You, Shiau-Yuan; Lin, Yu-Hsin; Tsai, Chih-Hung (Expert systems with applications, 2008)
A model is presented to address a steel supplier’s channel allocation problem that includes decisions of channel mix and capacity allocation for each distribution channel. The problem has been formulated as a fuzzy mixed integer multiple goal programming problem that includes business competitive advantages such as maximizing net profits, minimizing the rate of end user claims, and minimizing the rate of late lading, and is subject to constraints regarding manufacturing capacity, customer’s demand, channel capacity, channel quota flexibility, budget limitations, and so on. Realistic data from Taiwan’s largest steel company is implemented for the effectiveness of the model. The proposed model can also be applied to the allocation problem in other industries with preemptive priority and desired achievement level in a fuzzy environment.